Cultural Factors and their Effects on Organisational Justice. A Conceptual Framework for Malaysians Assessment Centres - Mohd Hanafiah, Ahmad; Ab Hamid, Mohd Rashid; Noor Azlinna, Azizan (2016)
This paper aims to explore how Malaysian cultures my influence the acceptance of assessment centres practice in Malaysia. Although assessment centres are are a popular technique that has been used and studied for at least 50 years, primarily in Western countries (Thornton & Rupp, 2006), there is a general lack of research into the implementation and effectiveness in developing countries in spite of a widespread growth in their use in recent years (Thornton & Krause, 2009). Therefore, it is important to understand how cultural differences may influence the implementation of assessment centres and how this might differ from its implementation in more developed nations. In this regards, this paper focuses on exploring the acceptance of assessment centres in Malaysia by using the organisational justice theory. Based on literature review, a conceptual framework of how the Malaysian culture may influence the acceptance of assessment centres in Malaysian public sectors will be proposed.